Multiculturalism as Indonesian National Identity in Political Satirical Comic Strip on Instagram - Agustinus Dias Suparto (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
The emergence of social media especially the popularity of Instagram has been used to facilitate people to share their thoughts in public discussion. Comic strip as a work of art which commonly aims as entertainment is also used to promote the value of the author in certain societal issues. Thus, comic strip such as KOSTUM or Komik Strip Untuk Umum (Comic Strip for Public) is using satirical jokes to share the idea of multiculturalism that has been challenged by people who use religious identity, ethnicity and political factions as the thing to differentiate others. Therefore, this paper will try to reveal how this comic strip promotes Indonesian national identity and how the author sees himself as the agent of multiculturalism.